2008
DOI: 10.1089/jop.2007.0120
|View full text |Cite
|
Sign up to set email alerts
|

Nonclinical Safety and Pharmacokinetics of Intravitreally Administered Human-Derived Plasmin in Rabbits and Minipigs

Abstract: The use of plasmin for pharmacologic vitreolysis and the creation of a posterior vitreous detachment offers several potential advantages over surgery. The nonclinical pharmacokinetics and safety of human-derived plasmin was evaluated following single or multiple intravitreal injections to rabbits and minipigs. Single intravitreal injections of plasmin at 45-900 microg resulted in a no adverse effect level (NOAEL) of 45 microg in both species; effects at higher doses included chemosis, mucopurulent discharge, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Previous studies have shown a maximal plasmin enzymatic activity between 15 and 60 minutes after injection [21] , [22] , decreasing thereafter and being either undetected after 24 hours [22] or detected at a very low level [21] . Because of the relatively short half-life of plasmin in the vitreous, the use of this enzyme seems to be well tolerated in the eye because it degrades in a short time following injection.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown a maximal plasmin enzymatic activity between 15 and 60 minutes after injection [21] , [22] , decreasing thereafter and being either undetected after 24 hours [22] or detected at a very low level [21] . Because of the relatively short half-life of plasmin in the vitreous, the use of this enzyme seems to be well tolerated in the eye because it degrades in a short time following injection.…”
Section: Discussionmentioning
confidence: 89%
“…The needle-penetration-point chosen for freehand injections in this study was in line with recently published data [17,18]. The needle-penetration-point of the device was fixed at 3.2 mm posterior to the limbus.…”
Section: Anatomical Location Of the Needle-penetration-pointmentioning
confidence: 90%
“…The injection angle of the device was fixed at 40˚ and this angle has proven to reliably miss the lens in the computer model and the printed eye model during the development phase. Commonly reported injection angles for freehand intravitreal injections in rabbits are approximately 45˚ or are described as directed into the mid-vitreous under direct visualization [17][18][19]. Our results show that none (0/11) of the injections made with the device (either with a 13-mm or 19-mm-needle) led to contrastagent-deposition touching the lens (see Figure 2 c for representative image), while this was the case in 67% (6/9) of freehand injections (see Figure 2 b for representative image).…”
Section: Evaluation Of Intravitreal Injection Devicementioning
confidence: 99%
See 1 more Smart Citation